Acute toxicological and behavioural effects of perfluorohexanoic acid (PFHxA) in the model nematode, Caenorhabditis elegans - Tanmoy Sana; Manjurul Islam Chowdhury; Panneerselvan Logeshwaran; Mallavarapu Megharaj (Environmental Challenges)
Perfluorohexanoic acid (PFHxA) has emerged as a significant environmental contaminant driven by the industrial transition to short-chain perfluoroalkyl substances. This study evaluates the behavioural toxicological impact of PFHxA on Caenorhabditis elegans, focusing on key endpoints including survival, locomotion, chemotaxis, reproduction, and growth. The median lethal concentration (LC50) was determined to be 521.3 mg L−1. Notably, exposure to PFHxA at concentrations as low as 0.31 mg L−1 resulted in significant reductions in reproduction, lifespan, body size, and head thrashing behavior. At 3.14 mg L−1, PFHxA further impaired chemotaxis learning and reduced body-bending frequency. The study also highlights the relationship between PFCA toxicity and chain length, with a toxicity gradient observed (PFOA >> PFHxA> PFBA). As the industry increasingly adopts short chain PFAS as alternatives to their long chain counterparts, PFHxA levels in the environment are expected to rise, particularly in regions impacted by firefighting foam usage. These findings highlight the importance of assessing the ecological risks associated with short chain PFAS. Importantly, this study is the first to demonstrate the toxic effects of PFHxA in nematodes, suggesting that PFHxA could pose a significant risk to non-target organisms such as C. elegans.